2014
DOI: 10.1038/srep05439
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Central Blood Pressure to Isometric and Isotonic Exercises

Abstract: Central blood pressure may be more closely associated with cardiovascular events than peripheral blood pressure. The aim of the present study was to investigate central blood pressure responses to exercise. Apparently healthy 18 subjects were enrolled in the study (38 ± 6 years) and changes in central and brachial blood pressure were recorded in response to ergometer and hand-grip exercises. Central blood pressure was estimated using an automated device (Omron HEM-9000AI). Systolic brachial blood pressure was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…44 Moreover, the novelty of our study is that we evaluated central blood pressure and arterial stiffness in elite powerlifting athletes, whereas Tanaka et al studied clinically healthy subjects from the general population. 40 In our study, subjects' mean brachial systolic and diastolic BP reduced by 8 and 2.4 mmHg, respectively. The results of our study support the evidence that strength training (combining dynamic and static exercise) has a significant BP-lowering effect in well-trained elite powerlifting athletes.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…44 Moreover, the novelty of our study is that we evaluated central blood pressure and arterial stiffness in elite powerlifting athletes, whereas Tanaka et al studied clinically healthy subjects from the general population. 40 In our study, subjects' mean brachial systolic and diastolic BP reduced by 8 and 2.4 mmHg, respectively. The results of our study support the evidence that strength training (combining dynamic and static exercise) has a significant BP-lowering effect in well-trained elite powerlifting athletes.…”
Section: Discussionsupporting
confidence: 43%
“…24,39 Previous research indicates that isometric and isotonic exercise may have a differential effect on brachial and central blood pressure. [40][41][42] Indeed, central systolic blood pressure was increased only after hand-grip, but not after ergometer exercises. 40 It has been suggested that peripheral arterial dilatation caused by isotonic exercise might reduce the amplitude of reflected pressure waves.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cardiovascular diseases (CVDs) may result from rheological 1 2 3 4 and hemodynamic 5 6 abnormalities. Among them, blood viscosity is considered as a crucial factor in determining the physiological and pathological conditions of CVDs 7 , because it augments flow resistance and wall shear stress, which stimulates the endothelial cells of blood vessels.…”
mentioning
confidence: 99%
“…[ 14 ] The clinical characteristics of BP reduction after a meal may be different in central and peripheral sites. Indeed, central and peripheral BPs differentially respond to various stresses such as physical exercise [ 15 ] and pharmacological interventions. The CAFÉ study [ 16 ] reported that individuals randomized to atenolol had a 4.3 mm Hg higher central systolic blood pressure than those given amlodipine, despite identical brachial BPs.…”
Section: Introductionmentioning
confidence: 99%